(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The present study aims to determining the criteria used in mate selection, and their relationship to some Demographic Variables (gender and academic specialization and years of study and dwelling-place). The sample consisted of (181) students. The researcher used mate selection criteria scale from her prepared. The results showed that mutual attraction and compatibility ideas and principles more traits of interest to the sample. There is significant statistical difference between males and females in the guise criteria in favor of males, and differences in psychological, financial and social criteria in favor of females. There is difference in the guise criteria in favor of students of scientific specialization, and difference in the financial criteria in favor of students of theoretical specialization. Also There is difference in the religious criteria in favor of final year students, against there is difference in the financial criteria in favor of first years students. While did not show differences in all criteria attribute to dwelling-place except the financial criteria in favor of rural students.